An innovative fuzzy logic frequency regulation strategy for two-area power systems - Nireekshana, Namburi; Ramachandran, R.; Narayana, Goddati Venkata (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
Modern environmentally friendly power system designs offer several application benefits, but they also generate losses. In order for this structured power system to operate reliably, the total generation, total load demand, and system losses must be balanced. Changes in load demand disrupt both the real and reactive power balances. As a result, the system frequency and tie-line interchange power differ from their planned values. A large variance in system frequency can cause the system to crash. Multiple connected area systems use clever load frequency control techniques in this scenario to deliver dependable and high-quality frequency and tie-line power delivery. In this case, a freestanding hybrid power system is considered, with generated power and frequency intelligently managed. In addition to the unpredictability of the wind, frequent changes in the load profile can result in significant and damaging power variations. The output power of such renewable sources may fluctuate to the point where major frequency and voltage variations occur in the system. The fuzzy logic PID controller (FLPIDC) is an intelligent approach recently proposed to address the load frequency control (LFC) issue of an interconnected power system. Standard proportional integral derivative (PID) controllers operate each section of the system.